Hematology, Biochemistry and Serum Protein Analyses of Antarctic and non-Antarctic Skuas - Ibañez, Andres Esteban; Najle, Roberto; Larsen, Karen Elizabeth; Montalti, Diego (Waterbirds)
Determination of hematological and biochemical parameters provides important data to assess the physiological condition in wild birds. Therefore, to carry out ecophysiology or conservation studies it is essential to establish baseline physiological parameters and how these change with age and life history events. Hematological (hematocrit, hemoglobin and erythrocyte sedimentation) and biochemical (glucose, total lipids and proteins, aspartate and alanine aminotransferase activities and electrolyte concentration) reference values were determined in two Antarctic migratory bird species, the Brown Skua (Stercorarius antarcticus) and South Polar Skua (S. maccormicki), from South Shetland Island during breeding season. Also, hematological data (hematocrit) were determined for non-Antarctic skuas, with Chilean (S. chilensis) and Falkland (S. antarcticus antarcticus) skuas sampled in the Beagle Channel islands (Tierra del Fuego Province) and Viana Island (Chubut Province), Argentina, respectively. Differences between adult Antarctic skua species were observed in hemoglobin, erythrocyte sedimentation, total lipids and aspartate aminotransferase activity. In addition, age-related differences in Antarctic skuas in hematocrit, hemoglobin, glucose and total protein values were observed. Serum reference protein fractions (Albumin, α1, α2, and globulins) were assessed by electrophoresis for Antarctic and non-Antarctic skuas. Similar protein patterns were observed between South Polar and Chilean skuas as well between Falkland Skua and Brown Skua. The differences between adult sympatric Antarctic skuas may be related to their nutritional status and species-specific migrations, feeding habits and the differential use of the breeding niches, while the age variation may be related to physiological development processes in chicks or to the energy expenditure in adults during breeding. Fil: Ibañez, Andres Esteban. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. División Zoología de Vertebrados. Sección ...